Extraction and Characterization of Essential Oil From Lemongrass (Cymbopogon Citratus) by Microwave-Assisted Hydrodistillation - Nour, A. H.; Ranitha, Mathialagan; Azhari, H. Nour; Ahmad Ziad, Sulaiman (2013)

(untitled)
The increasing demand of essential oil has opened up wide opportunities for global marketing and this leads to the requirement of competitive product in market which comes with all the advantages in term of cost, quality and its production time. Essential oil is a volatile component. Therefore, it is vital to identify a best extraction technique. Microwave-assisted hydrodistillation (MAHD), an advanced distillation method that take advantage of microwave heating with the conventional hydrodistillation, recently been widely used for the extraction of essential oil from medicinal plants and herbs due to its economic and green technology. This study was carried out to determine the performance of MAHD in the extraction of essential oil from Lemongrass (Cymbopogon Citratus). The effect of three main factors which were microwave power, extraction time and water to raw material ratio were investigated. As a result, the best condition that has been determined for maximum essential oil production were under 250 W microwave power for 90 minutes of extraction at water to raw material ratio of 8:1. This optimum condition was finalized based on its maximum yield from Lemongrass (Cymbopogon Citratus) which was 1.37% (w/w). Then, the oil samples have been analyzed by using GC-MS to authenticate that the microwave irradiation did not adversely influence the composition of essential oils. The components detected in the essential oil of Lemongrass (Cymbopogon Citratus) were Citral, (Z) Citral, β-mycrene and Borneol. The dominant component in the essential oil of Lemongrass (Cymbopogon citratus) was Citral. The maximum oil yield from Lemongrass (Cymbopogon citratus) was obtained at shorter extraction period without significant effect on their chemical constituents. Moreover, this extraction has been successfully done without any chemical aid with a significant yield. This may prove MAHD as a cost effective method and also expected would bring volume of worth in the essential oil production industry.